Analytic methods in sports : using mathematics and statistics to understand data from baseball, football, basketball, and other sports /: using mathematics and statistics to understand data from baseball, football, basketball, and other sports. (2014) - Severini, Thomas A (Thomas Alan), 1959-
No abstract available